Blue Horizontal Branch Stars in Pan-STARRS. Issue 67 (17th July 2015) - Vickers, J.J.; Huxor, A.P.; Grebel, E.K.
Abstract : We discuss the selection of blue horizontal branch stars (BHBs) using preliminary Panoramic Survey Telescope and Rapid Response System (Pan-STARRS) color data and outline techniques for structure detection using those data. We first outline the adaptation of an old color selection for for BHBs using Sloan Digital Sky Survey (SDSS) data to the Pan-STARRS filter set. We next outline a rudimentary search algorithm designed to autonomously detect substructure in the Galactic halo. Finally we discuss preliminary results and comment on future refinements to the process.